Antillopsyche sessilis, new genus and species, a new Psychidae (Lepidoptera: Tineoidea) from Cuba with an unusual larval feeding behavior - Aguila, Rayner Núñez; Davis, Don R. (Zootaxa, 2016)
A new genus and species, Antillopsyche sessilis Núñez & Davis, of Psychidae are described from Cuba, West Indies. The new taxon shares certain features with some members of the subfamily Arrhenophaninae but more with the larvae and the fully winged adult females of other subfamilies of Psychidae. Antillopsyche has been assigned provisionally to the subfamily Typhoniinae based on these similarities. Several aspects of its larval biology are described, including the sessile larval cases and foraging behavior, both unique among the known Psychidae. An undescribed species of Dryadaula Meyrick, 1893 (Dryadaulidae) was found inhabiting the larval cases of A. sessilis, but their ecological relationships remain unclear. Other ecological data for Antillopsyche such as distribution, habitat, and parasitoids are also provided.